An Analysis of Students’ Difficulties in Speaking English - Lado, Noviyana; Amalyasari, Maya Rizki; Lestari, Hernina Dewi (UIBU, 2024)
Speaking ability in English is a core skill that reflects a learner’s overall language proficiency. However, many students still encounter various obstacles when attempting to speak. This study examines the speaking difficulties faced by eighth-grade students at SMP N 2 Waikabubak. The purpose of this research is to identify the types of difficulties students experience and the factors contributing to those challenges. The participants in this study were eighth-grade students and English teachers at SMP N 2 Waikabubak. A descriptive qualitative approach was employed, with data collected through observation checklists and interviews. Interview responses were gathered from students, and the data were analysed through stages of observation checklist review, transcription, data reduction, data display, and conclusion drawing. The findings indicate that students’ speaking difficulties stem from two main sources: linguistic and psychological factors. Linguistic barriers include limited vocabulary, poor pronunciation, and inadequate grammar. Psychological factors involve low self-confidence, shyness, anxiety, and fear of making mistakes.